Role of miR-653 and miR-29c in downregulation of CYP1A2 expression in hepatocellular carcinoma - Krkoška, Martin; Nekvindová, Jana; Nevědělová, Kateřina; Zubáňová, Veronika; Radová, Lenka; Vondráček, Jan; Herůdková, Jarmila; Slabý, Ondřej; Kiss, Igor; Bohovicová, Lucia; Fabian, Pavel; Tylichová, Zuzana; et al. (Pharmacological reports, 2022)
BACKGROUND: Hepatocellular carcinoma (HCC) is a major contributor to the worldwide cancer burden. Recent studies on HCC have demonstrated dramatic alterations in expression of several cytochrome P450 (CYP) family members that play a crucial role in biotransformation of many drugs and other xenobiotics; however, the mechanisms responsible for their deregulation remain unclear. METHODS: We investigated a potential involvement of miRNAs in downregulation of expression of CYPs observed in HCC tumors. We compared miRNA expression profiles (TaqMan Array Human MicroRNA v3.0 TLDA qPCR) between HCC human patient tumors with strong (CYP-) and weak/no (CYP+) downregulation of drug-metabolizing CYPs. The role of significantly deregulated miRNAs in modulation of expression of the CYPs and associated xenobiotic receptors was then investigated in human liver HepaRG cells transfected with relevant miRNA mimics or inhibitors. RESULTS: We identified five differentially expressed miRNAs in CYP- versus CYP+ tumors, namely miR-29c, miR-125b1, miR-505, miR-653 and miR-675. The two most-upregulated miRNAs found in CYP- tumor samples, miR-29c and miR-653, were found to act as efficient suppressors of CYP1A2 or AHR expression. CONCLUSIONS: Our results revealed a novel role of miR-653 and miR-29c in regulation of expresion of CYPs involved in crucial biotransformation processes in liver, which are often deregulated during liver cancer progression.
Keywords: cytochrom P-450 CYP1A2; nádory jater; Biotransformation; Hepatocellular carcinoma; regulace genové exprese u nádorů; Humans; Down-Regulation; MicroRNAs; microRNA; Cytochrome P-450 CYP1A2; lidé; Xenobiotics; Liver Neoplasms; CYP1A2; down regulace; xenobiotika; nádorové buněčné linie; biotransformace; Hepatocytes; mikro RNA; Cell Line, Tumor; Gene Expression Regulation, Neoplastic; hepatocyty; AHR; Carcinoma, Hepatocellular; hepatocelulární karcinom